Legal and Business Ethics Training in Inventory Management - Ardiansyah Rasyid; Cicelya Alvina; Cristian Wijaya; Niken Amberta (CV. Proaksara Global Transeduka, 2025)
The retail business does not only consider profits, but also social responsibility towards consumers and society. Businesses must realise that the choices they make when purchasing goods can affect the company's reputation and consumer trust. Honesty, transparency, and fairness must be upheld in every transaction. The partners involved in the current community service (PKM) activities are engaged in the textile retail industry and are located in the Tanah Abang market. The main problem lies in the partners' lack of knowledge about the legal and ethical aspects of running a business. The activities were carried out through training related to legal and ethical issues. The training was conducted online via the Zoom platform. Through this activity, it is hoped that the problems arising in the partners' businesses will be resolved, and the partners will be able to increase their knowledge of ethical practices that consider the social and environmental impacts of their business when purchasing goods. Based on the results of this activity, it is recommended that business actors pay attention to legal and ethical aspects in the process of buying merchandise, in order to avoid legal risks and maintain good relationships with consumers and suppliers. As such, they should be able to uphold ethical values towards customers.